A History of the Hemp Industry in Kentucky - Hopkins, James F. (Book collections on Project MUSE., 1998)
It is hard to believe that at one time burley tobacco was not the chief cash crop in Kentucky. Yet for more than half a century hemp dominated the state's agricultural production. James Hopkins surveys the hemp industry in Kentucky from its beginning through its complete demise at the end of World War II, describing the processes of seeding and harvesting the plant, and marketing manufactured goods made of the fiber. With debate presently raging over the legalization of industrial hemp, it is essential that an accurate portrait of this controversial resource be available. Although originally pub.